A mechanism of failure in shear bands. (September 2018) - Torki, Mohammad E.; Benzerga, Ahmed Amine
Abstract: We have carried out dilatant plasticity simulations to investigate the process of void-mediated failure inside a shear band. The constitutive model accounts for possibly inhomogeneous flow within the band, void rotation and void elongation. We found that the material in the band may soften with no increase in the void volume fraction. For a given matrix hardening capacity, the rate of softening was found to depend strongly on the ratio of shear band width to in-plane void spacing. The emergent softening led to complete loss of load bearing capacity thereby providing a physical mechanism of failure in shear bands. The mechanism is consistent with essential features of shear-fractured specimens in terms of surface roughness, porosity and dimple shape.